Dominance of attentional focus: a comparative study on its impact on standing postural control in healthy younger and older adults - Sawai, Shun; Murata, Shin; Sakano, Yuya; Fujikawa, Shoya; Yamamoto, Ryosuke; Shizuka, Yusuke; Nakano, Hideki (Frontiers in Human Neuroscience, 2024)
Attentional focus is a phenomenon in which shifting the focus of attention alters performance of standing postural control. It can be categorized as internal focus (IF), which directs attention to the body parts, or external focus (EF), which directs attention to the external environment. Although attentional focus that improves standing postural control in younger people exhibits individual dominance, the dominance of attentional focus in standing postural control in older adults remains ambiguous. Therefore, this study aimed to compare the dominance of attentional focus in standing postural control between healthy younger and older adults, a crucial step for understanding the aging process. The participants performed a standing postural control task under the IF and EF conditions. Based on the condition during which they exhibited superior performance, the participants were divided into two groups: IF-dominant and EF-dominant. The standing postural control performance in each group under the IF and EF conditions was subsequently compared. The results showed that the participants, encompassing both younger and older adults, were divided into the IF-dominant and EF-dominant groups, confirming the dominance of attentional focus. The performance under the EF condition in older adults was also influenced by the dominance of attentional focus. These results highlight the potential importance of intervention methods based on the dominance of attentional focus, providing valuable insights into future research and clinical practice.